2009
DOI: 10.1002/ppap.200900028
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Growth of Photoactive Titania by Atmospheric Pressure Plasma

Abstract: Atmospheric pressure glow discharge plasma CVD was used to deposit thin films of titania at 200 8C using two different precursors. The resulting films were characterised using techniques including XPS, RBS and XRD. It was established that annealing at temperatures as low as 275 8C produced crystalline films that were photocatalytically active. When annealed at 300 8C the photoactivity was greater than that of commercially available ''self-cleaning'' titania films. The effects of the different precursors, annea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…However, the challenge still remains as to how to prevent rapid oxidation of TiCl 4 and deposit stoichiometric TiO 2 film instead of powder on the substrate. HODGKINSON et al [19] found that the deposition of TiO 2 film from TiCl 4 and O 2 using He as the working gas was highly sensitive to oxygen partial pressure. When p O2 /p TiCl4 = 1/3, a layer of well adhered and scratch resistant film was formed, but the film composition was substoichiometric (TiO x , x ≈ 1.6 ∼ 1.7), while further increasing p O2 /p TiCl4 to 2/3 resulted in powder formation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the challenge still remains as to how to prevent rapid oxidation of TiCl 4 and deposit stoichiometric TiO 2 film instead of powder on the substrate. HODGKINSON et al [19] found that the deposition of TiO 2 film from TiCl 4 and O 2 using He as the working gas was highly sensitive to oxygen partial pressure. When p O2 /p TiCl4 = 1/3, a layer of well adhered and scratch resistant film was formed, but the film composition was substoichiometric (TiO x , x ≈ 1.6 ∼ 1.7), while further increasing p O2 /p TiCl4 to 2/3 resulted in powder formation.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric barrier discharge (DBD) is a simple and easily operated approach for generating AP cold plasma, and has recently been adopted for the preparation of TiO 2 nanopowder or film 10–17. In these studies, AP volume‐DBD plasma was commonly used, typically using inexpensive and volatile TiCl 4 and O 2 as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…For the PCVD process, AP non‐thermal plasma has been increasingly used to deposit TiO 2 thin film due to the reactor design simplicity which doesn't require any vacuum system. But many researches have shown that the as‐deposited TiO 2 thin films were of amorphous structure 8–10, 20. In our previous paper,8 surface DBD with 15 kHz AC power supply was used for the deposition of TiO 2 films, and the as‐deposited TiO 2 films showed an amorphous structure, as determined by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 97%
“…Titanium dioxide (TiO 2 ) films, because of their special properties, have been studied extensively as semiconductor photocatalysts for solar‐energy conversion, and purification of water and air 1–6. The deposition of TiO 2 film has been conducted by both wet‐ and dry‐coating processes, such as sol‐gel coating, thermal CVD, and plasma (P)CVD 7–19…”
Section: Introductionmentioning
confidence: 99%